Online Energy Management System (EMS) Including Engine and Catalyst Temperatures for a Parallel HEV. Issue 1 (July 2017) - Maamria, D.; Sciarretta, A.; Chaplais, F.; Petit, N.
Abstract: In this paper, a first practical extension of the Equivalent Consumption Minimization Strategy (ECMS) is proposed to include thermal dynamics (engine and catalyst temperatures) in the optimal design of an Energy Management System (EMS) for a parallel Hybrid-Electric light-duty Vehicle (HEV). The task of this novel multi-state ECMS is to achieve a sufficient level of performance with respect to pollutant emissions while keeping fuel consumption within acceptable limits. The extension suggested here is based on correlations between the thermal state and their corresponding adjoint states, observed along extremal calculated from extensive offline solutions of optimal control problems. Simulation results stress that the obtained performance is sufficient to satisfy the environmental norms while keeping fuel consumption sub-optimality relatively marginal.